(In)Equality and (In)Justice - Guillermina Jasso (Institute for the Study of Labor (IZA), 2016)
Understanding the exact connection between inequality and justice is important because justice is classically regarded as the first line of defense against self-interest and inequality. Absent a strong and clear link between inequality and justice, the sense of justice would not awaken to exert its moral suasion, no matter how great the inequality or how fast its increase. We obtain exact links between economic inequality and three parameters of the justice evaluation distribution–the mean, median, and variance–across a comprehensive set of inequality measures and a substantial starter set of just reward scenarios. This work shows that there is no general necessary connection between inequality and justice–inequality effects can be nonexistent, or can occur in opposite directions. There is, however, a striking pattern in some justice situations: As economic inequality increases, the average of the justice evaluations moves leftward, deeper into the territory of unjust underreward, and the distribution stretches outward, increasing the gulf between underrewarded and overrewarded and hollowing out the middle class. Further work specifying and strengthening the logical foundation will help guide development of sharp new empirical strategies for deeper understanding of the inequality-justice connection in all its manifestations.
Keywords: C02; C65; D31; D6; I3; 330; lognormal distribution; fairness; justice; inequality; Pareto distribution; power-function distribution; Gini coefficient; Atkinson inequality; Theil MLD; general inequality parameter; justice evaluation; justice evaluation function; justice evaluation distribution